Practices of Pica among Pregnant Females and Associated Outcomes in Newborn and Pregnant Women - Farhana Jabeen Shah, Abdul Matin Qaisar, Iftikhar Ali Malik, Ruqqia Jahangir, Fareeha Rahman, Wardah Anwar-Ul-Amin (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To find out the females practicing pica and its effects in newborns. Study Design: Cross-sectional descriptive study Place and Duration of Study: Department of Community Medicine, Kabir Medical College Peshawar from 1st May 2021 to 31st December 2021. Methodology: Three hundred and eighty six pregnant women from 15 to 49 years were enrolled. The WHO standards for new born weight were used to measure normal and underweight babies and associated factors causing anemia and pica practicing among females. A semi-structured questionnaire was used to collect data on socioeconomic conditions, family size, maternal education, parity, gravidity and complication during and after delivery. Results: The prevalence of maternal anemia 73.3% in mothers of aged 15 to 49 years. Antenatal visits, medications used during pregnancy, and intake of non-food (pica) items showed significant results with p<0.05 and showed strong association between maternal factors and newborn weight. Age, ethnicity, socioeconomic status, parity, gravidity, body mass index, history of genetic disorder factors showed non-significant results. Conclusions: The practicing pica and other factors causing anemia cause low birth weight in new born while location or place of living did not affect the weight of the new born.